Uma engenharia didática para o ensino das operações com números racionais por meio de calculadora para o quinto ano do ensino fundamental - Oliveira, Antonio Sergio dos Santos de (2015)
This paper had the objective of making a group of students from the fifth grade to build meaning to the fundamental operatorial rules with fractional numbers by using scientific calculators with fractional representation. With this in mind, we developed a sequence of teaching with four students of a public school located in the suburb of Belém-PA. We based our theories on the Theory of Didactic Situations (TDS) (Teoria das Situações Didáticas-TSD) and the Theory of Record of Semiotic Representation and the Didactic Engineering as methodology. The TDS helped us to elaborate, experiment and analyze the results of the sequence, while the Theory of Record of Semiotic Representation helped us to articulate among the figure and numeric records. In the analysis of the activities, we verified that the students after using the scientific calculator, they managed to verbalize and write rules to the addition and subtraction of fractional numbers with the same denominator to a multiplication of any fractional numbers and to the division of fractional numbers that presented not only the numerators but also the multiple denominators. However, the students managed not only by using the calculator to perceive the rules for the addition and division of any fractional numbers. We understand that the calculator allowed the students to search for relations and dot not treat the fractional numbers only as two natural numbers. We also should probably have related to other didactic resources so that they could have perceived the relations between numerators and denominators for the addition and subtraction operations